Herpes zoster vaccine coverage in Australia before and after introduction of a national vaccination program. Issue 20 (29th April 2020) - Lin, Jialing; Wood, James G.; Bernardo, Carla; Stocks, Nigel P.; Liu, Bette
Abstract: Background: In Australia, a herpes zoster (HZ) vaccination program targeting adults aged 70 years old with catch-up for those 71-79 years began in November 2016 but there is limited information on vaccine uptake and coverage achieved since commencement. Methods: We used a national de-identified electronic primary care dataset, MedicineInsight, and extracted records from patients turning 50–90 years old during 2016–2018. Among patients considered regular attenders, with at least one visit per year in the two years prior, we estimated the crude and adjusted average monthly HZ vaccine uptake in the target population (70–79 years old) for each year since program implementation as well as cumulative vaccine coverage until December 2018. Multivariate logistic regression was used to analyse characteristics associated with higher coverage. Results: Among 52, 229, 55, 034, and 57, 316 regular attenders turning 70–79 years old in 2016, 2017 and 2018 respectively, the average monthly vaccine uptake rate was 5.5%, 3.3%, and 1.6% respectively. Up to 31st December 2018, the estimated cumulative vaccine coverage in regularly attending adults was 46.9% (25, 791/55, 034). It was substantially lower at 41.6% (27, 040/65, 010) using an alternate definition of a regular attender. Vaccine coverage differed by sex (women: 48.5% versus men: 45.1%, adjusted OR = 1.1, 95% CI: 1.1–1.2); by jurisdiction (compared to New South Wales: 43.7%, South Australia: 55.6%, aOR = 1.6, 95% CI (1.5–1.8); Northern Territory: 27.6%, aOR = 0.6, (0.5–0.7)); by remoteness status (compared to major cities: 47.6%, remote/very remote areas: 38.2%, aOR = 0.7, (0.6–0.8)); and by socioeconomic disadvantage (compared to most disadvantaged: 41.8%, most advantaged: 48.6%, aOR = 1.6 (1.2–2.1)). Conclusions: Our estimates of HZ vaccine coverage are substantially higher than the only other reports based on the Australian Immunisation Register however they still suggest that uptake is suboptimal. The use of electronic medical records can complement other data for estimating vaccine coverage in Australian adults.